Exploring Math Anxiety in Prospective Mathematics Teachers: A Phenomenological Study of Mathematics Education Students at Singaperbangsa Karawang University - Talenta Valentina Christi; Annisa Maiyada; Fitria Dwi Khaerunnisa; Lita Dewi Firstianti; Nurhaliza Salsabiela Hanum; Rahmanda Putri (Jurnal Didactical Mathematics, 2026)
Mathematics anxiety remains a persistent challenge among prospective mathematics teachers, influencing cognitive performance, emotional regulation, and instructional readiness. However, existing studies predominantly rely on measurement-based approaches and provide limited insight into how anxiety is experienced across different academic contexts, particularly between examination and teaching situations. This study aims to investigate the lived experiences of mathematics anxiety among undergraduate students in a Mathematics Education program at Singaperbangsa Karawang University, Indonesia. A qualitative phenomenological design was employed to capture participants’ subjective experiences. Participants were selected through purposive sampling based on their experience in both mathematics examinations and teaching practice. Data were collected through semi-structured, in-depth interviews, supported by a preliminary screening questionnaire, and analyzed using an interactive thematic approach. The findings reveal that mathematics anxiety is a multidimensional and context-dependent phenomenon, manifesting across four interconnected domains: cognitive, attitudinal, somatic, and mathematical knowledge. The mathematical knowledge domain emerges as the primary source of anxiety, driven by conceptual insecurity. This condition triggers a cascade of effects, disrupting cognitive processing, evoking emotional avoidance, and generating physiological responses. Anxiety is found to be more pronounced in teaching contexts, where real-time explanation and public performance intensify pressure. This study contributes by offering an integrated, experience-based understanding of mathematics anxiety, emphasizing the dynamic interaction between cognitive, affective, and contextual factors. The findings highlight the need for teacher education programs to integrate conceptual support with emotional regulation and adaptive coping strategies to enhance both learning and teaching readiness.